Pola Komunikasi Orang Tua Dalam Perkembangan Psikologi Pada Anak Usia Remaja - Nursaady Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This literature review aimed to investigate parental communication patterns in the development of psychology in adolescence. The primary and secondary data were obtained from books and articles written by experts which were carefully discussed regarding the previously determined focus. The result of the study shows that communication patterns must be built in the psychological development of adolescents by using the language that they understand most, establishing good basic internal relationships between parent and adolescents, showing a positive attitude towards children with polite words and actions, then also showing attention to them, taking care of their weaknesses by not exposing them, do not judge their mistakes, treat children with full of love and affection, showing a deep understanding to them. Subsequently, advice can be conveyed while providing more time for the adolescence